pls give me solution of this question ☝
Attachments:
![](https://hi-static.z-dn.net/files/d79/4867e7cfdc0d496b96c3d7f5b18509d7.jpg)
Answers
Answered by
0
Hey Mate here's your answer:
- Given a , b , c are in continued proportion
⇒ a : b : : b : c ⇒ a x c = b x b
ac=b² .............(1)
- Now A/Q a(b-c)=2b ⇒ ab - ac -2b = 0
⇒ ab - b² -2b = 0
⇒ b(a - b -2) = 0
⇒ a - b -2 =0 as b≠0
⇒ a - b = 2 ............(2)
- Now to prove a-c=2(a+b)/a
LHS = a-c ⇒ multipying a to nr. and dr.
⇒ a(a-c)/a ⇒ a² - ac/ a ⇒ a² - b² / a
⇒ (a-b)(a+b)/a ⇒ 2(a+b)/a from (1) and (2)
Hence proved
Hope this helps and if it does then please mark my my answer as the Brainliest.
Similar questions